Advancements in photovoltaic technology: A comprehensive review of recent advances and future prospects - Abdelrahman O. Ali; Abdelrahman T. Elgohr; Mostafa H. El-Mahdy; Hossam M. Zohir; Ahmed Z. Emam; Mostafa G. Mostafa; Muna Al-Razgan; Hossam M. Kasem; Mohamed S. Elhadidy (Energy Conversion and Management: X)
Photovoltaic (PV) technology has become a cornerstone in the global transition to renewable energy. This review provides a comprehensive analysis of recent advancements in PV technology and presents forward-looking insights into future trends. Beginning with a historical overview and the fundamental principles of photovoltaic conversion, the paper traces the evolution of commercial PV cells, such as crystalline silicon and thin-film technologies. Special attention is given to emerging materials, including perovskite, multi-junction, and organic photovoltaic cells, which hold significant promise for boosting solar energy conversion efficiency. The paper also explores cutting-edge innovations in PV device architectures, such as tandem cells, quantum dot cells, bifacial panels, flexible PV, and transparent solar cells, highlighting their potential in diverse applications. Key manufacturing processes and efficiency enhancement techniques, including silicon wafer production and thin-film deposition, are thoroughly examined. The review further explores the integration of PV systems into smart grids and building management systems, supported by real-world case studies. Economic and environmental analyses underscore the pivotal role of PV technology in reducing carbon emissions and fostering sustainable energy solutions. Finally, the review addresses pressing challenges, such as efficiency constraints, sustainability issues, and recycling concerns, while proposing directions for future research aimed at overcoming these hurdles and driving continued innovation in the field.